The Role of Organizational Citizenship Behavior in Mediating Work Motivation and Job Satisfaction on Employee Performance at the Medan Religious Education and Training Center - Muhammad Ibrahim; Mesra B (CV. AFDIFAL MAJU BERKAH, 2024)
Organizational Citizenship Behavior abbreviated as (OCB) is a personal attitude that every employee who works in both government and private agencies must have. This research was conducted to determine the role of OCB in mediating work motivation and job satisfaction on employee performance at Religious Education and Training Centers. Medan. This research was conducted at the Medan Religious Education and Training Center Office, but because the population was relatively small, the sampling technique used was a saturated sample technique, which involved all respondents to become samples, meaning the sample that would be used was 76 employees. Research data was collected by distributing questionnaires and primary data sources were also used in drawing samples. This research model uses analytical skills and the measuring tool uses Smart PLS 3. The results of this research are as follows: Organizational Citizenship Behavior plays a role in mediating work motivation and job satisfaction on the performance of Medan Religious Education and Training Center employees. Work motivation plays a role in increasing performance, Work Motivation plays a role in improving employee performance, work satisfaction plays a role in improving employee performance and Organizational Citizenship Behavior plays a role in improving employee performance.